Kinetic Study of Leuco‐Indigo Carmine Oxidation and Investigation of Taylor and Dean Flow Superposition in a Coiled Flow Inverter. Issue 10 (4th July 2019) - Krieger, Waldemar; Hörbelt, Max; Schuster, Simon; Hennekes, Julian; Kockmann, Norbert
Abstract: In two‐phase capillary flow, Taylor and Dean vortices can enhance mass transfer according to recent studies. By utilizing a colorimetric method based on the consecutive oxidation of leuco‐indigo carmine it is possible to visualize the superposition of Taylor and Dean vortices in a gas‐liquid system. A kinetic study is performed in order to estimate the enhancement factor. Depending on the flow conditions, three different flow regimes are identified with different intensities of Taylor and Dean vortices affecting the oxygen distribution within the liquid phase. A dimensionless number is derived that describes this transition in flow regimes. Abstract : Superposition of Taylor and Dean vortices for a gas‐liquid system is visualized by utilizing a colorimetric method. Depending on the flow conditions, different flow regimes are identified with varying intensities of Taylor and Dean vortices affecting the gas distribution within the liquid phase. A dimensionless number is derived that describes this transition in flow regimes.